2012
DOI: 10.3892/ijmm.2012.897
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between serum undercarboxylated osteocalcin and hyaluronan levels in patients with bilateral knee osteoarthritis

Abstract: Abstract. Serum undercarboxylated osteocalcin (s-ucOC) is a marker for vitamin K metabolism (deficiency). The aim of this study was to investigate the serum levels of ucOC in patients with bilateral knee osteoarthritis (K-OA), and the correlation between ucOC and other biomarkers for K-OA. A total of 25 patients (22 women, 3 men, mean age 76.0±7.8, range 54-88 years, mean BMI 24.9±4.7) with a Kellgren-Lawrence grade of 3 or 4 for bilateral knee were enrolled in this study. The levels of s-ucOC and other biomar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 17 publications
1
16
0
1
Order By: Relevance
“…Accordingly, recent studies have demonstrated a clear association between knee OA and subclinical vitamin K insufficiency [7][8][9], but none of them has considered GRP as a target protein. Our results showing a relation between GRP and MGP ␥-carboxylation deficiency and OA are also in agreement with recent findings, suggesting that vitamin K metabolism may be associated with synovitis in OA patients, and that serum undercarboxylated OC could be a biomarker for OA [38]. The novel association of both phylloquinone (vitamin K1) and menaquinone (vitamin K2) deficiency with the disease further suggests the use of vitamin K as a potential therapeutic/prophylactic agent for OA [39].…”
Section: Discussionsupporting
confidence: 92%
“…Accordingly, recent studies have demonstrated a clear association between knee OA and subclinical vitamin K insufficiency [7][8][9], but none of them has considered GRP as a target protein. Our results showing a relation between GRP and MGP ␥-carboxylation deficiency and OA are also in agreement with recent findings, suggesting that vitamin K metabolism may be associated with synovitis in OA patients, and that serum undercarboxylated OC could be a biomarker for OA [38]. The novel association of both phylloquinone (vitamin K1) and menaquinone (vitamin K2) deficiency with the disease further suggests the use of vitamin K as a potential therapeutic/prophylactic agent for OA [39].…”
Section: Discussionsupporting
confidence: 92%
“…1,2 According to the World Health Organization (WHO) Scientific Group on Rheumatic Diseases, 10% of the world's population older than 60 years has significant clinical problems that can be attributed to OA. [3][4][5] Obesity, trauma, age, genetic factors, and mechanical forces constitute risk factors and can initiate the process of cartilage degeneration. 6,7 Furthermore, clinical symptoms involve joint pain, stiffness, local inflammation, and loss of mobility, which lead to a significant reduction of the quality of life.…”
mentioning
confidence: 99%
“…Higher OC levels were significantly correlated with decreased rates of cartilage loss and radiologic progression of knee OA (56,57). In contrast, Naito et al (58) have demonstrated that OC levels were not elevated in patients with OA. Similarly, Jung et al (59) found no relationship between serum OC concentrations and ultrasonographic findings of knee OA.…”
Section: Ykl-40mentioning
confidence: 85%